Vaccinating with SRP E. coli does not affect feeder cattle performance, health, or carcass characteristics - D.J. Rezac; B.A. Butler; Daniel U. Thomson; Benjamin W. Wileman; Christopher D. Reinhardt (Kansas Agricultural Experiment Station Research Reports, 2012)
Siderophore-receptor and porin-based (SRP) Escherichia coli vaccine technology functions by starving the E. coli organism via competitive exclusion for proteins that scavenge iron, an essential nutrient for E. coli viability. Vaccination with SRP E. coli technology decreased the prevalence of E. coli O157:H7 in artificially inoculated cattle and in cattle naturally shedding the organism. Examination of the effects that SRP E. coli vaccines exert on performance parameters has yet to be attempted in a commercial setting. The use of SRP E. coli vaccine technology effectively decreases the prevalence of E. coli O157:H7 in feeder cattle and may improve beef safety; however, the vaccine's effects on the economics of cattle feeding are unknown. Therefore, the objective of our study was to assess the effects of vaccinating cattle three times with an SRP E. coli vaccine verses a placebo on performance, health, and carcass characteristics of cattle fed in commercial feedlots.
Keywords: Cattlemen' s Day; 2012; Kansas Agricultural Experiment Station contribution; no. 12-231-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1065; Beef Cattle Research; 2012 is known as Cattlemen' s Day; Beef; E.coli; Feeder cattle; Performance; Health; Carcass characteristics